Analysis of Jurisdiction Effectiveness in Conducting Ghaib Calls Through Mass Media in Kraksaan Religious Court - M. Fajri Maulana Ahkam; Fathullah Rusly; Vita Firdausiyah (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2023)
This study discusses the effectiveness of bailiffs in making summons from the occult through the mass media at the Kraksaan Religious Court. Then the sub-topic of the discussion is the occult summons process carried out by the Kraksaan Religious Court and the efforts made by the court to optimize the occult summons. The purpose of this study is to find out the implementation of occult summons through the mass media and their effectiveness at the Kraksaan Religious Court. This research was conducted at the Kraksaan Religious Court using a descriptive qualitative research type. Data acquisition is taken from primary and secondary data. The data acquisition method is by means of interviews and taking from data concerning magical summons. In the process of summoning ghoib cases, the use of mass media such as newspapers, bulletin boards, and radio broadcasts is no longer effective at this time. So that it is necessary to update the regulations or suggestions from the author regarding this matter, because they are no longer in accordance with social conditions in the digitalization era, there is a need to renew the conventional method of summoning the occult.